All Days 2013
DOI: 10.2118/165274-ms
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Value of Polymer Flood Project with Proactive Well and Reservoir Management

Abstract: In viscous oil reservoirs, Polymer flooding is often used to improve oil recovery either after a short period of waterflooding or as a tertiary recovery process following extensive period of waterflood. After six years of water flooding in a major reservoir in Sultanate of Oman having viscous oil (90cp), a field development plan was developed to implement polymer flooding in this reservoir with anticipated incremental oil recovery of around 10% over and above that of waterflood. Necessary facilities were const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…• Workovers and well stimulation to restore well productivity (Al-Kalbani et al, 2014a;Choudhuri et al, 2013;Christopher et al, 1988;Kumar et al, 2016).…”
Section: Summary Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…• Workovers and well stimulation to restore well productivity (Al-Kalbani et al, 2014a;Choudhuri et al, 2013;Christopher et al, 1988;Kumar et al, 2016).…”
Section: Summary Discussionmentioning
confidence: 99%
“…Finally, Haynes, A. K., Clough, M. D., Fletcher, A. J. P., & Weston, S., (2013) reported that the rate at which fracture growth occurred was unknown. Choudhuri et al, 2013;Choudhuri et al, 2014;Koning and Mentzer, 1988;Shuaili et al, 2012;Thakuria et al, 2013;Zwaan and Valdez, 2015). This field was discovered in 1956 and started commercial production in 1980.…”
Section: Polymer Injection Ratesmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned by Choudhuri et al (2013), one reason for this is the large amount of polymer required per unit of recovered oil. This affects which patterns to roll out to polymer flooding, how long to inject polymer before incremental gains are compared with base waterflood performance, and what the optimal slug-size and polymer concentration should be.…”
Section: Introductionmentioning
confidence: 99%